Ocular morbidity among primary school children of Dhulikhel, Nepal - Sherpa, D; Pant, CR; Joshi, N (Nepalese Journal of Ophthalmology, 2011)
Background: Knowledge of disease pattern in children can help design preventive and curative strategies. Objective: To study the pattern of ocular morbidity among the primary school children. Subjects and methods: All the children of randomly-selected five government primary schools of Dhulikhel were included in this study. A complete eye examination was done in all children including color vision, loupe examination, refraction and Schiotz tonometry. Funduscopy and automated perimetry were done in selected children. Results: A total of 466 primary school children were included in the study, of which 466 children 47 (10.08 %) had ocular morbidity. Refractive error was the commonest type of ocular morbidity in 11 (2.36 %). Hypermetropia was the commonest type of refractive error (0.84 %) in contrast to myopia (0.64 %). Conjunctivitis was the second common type of ocular morbidity (1.71 %). Glaucoma suspects accounted for 1.28 %, xexophthalmia 1.07 %, blephatitis 0.85 %, amblyopia 0.43 %, color blindness 0.43 %, conjunctival nevus 0.43 %, glaucoma 0.43 %, and strabismus 0.43 %, while congenital abnormalities were less common. Conclusion: Refractive error is the commonest form of ocular morbidity in primary school children. Key words: primary school children, refractive error DOI: http://dx.doi.org/10.3126/nepjoph.v3i2.5272 Nepal J Ophthalmol 2011; 3(2): 172-176